2011
DOI: 10.1097/inf.0b013e31822d28df
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Human Papillomavirus-16/18 AS04-adjuvanted Vaccine Coadministered With Tetanus Toxoid, Reduced Diphtheria Toxoid, and Acellular Pertussis Vaccine and/or Meningococcal Conjugate Vaccine to Healthy Girls 11 to 18 Years of Age

Abstract: Concomitant administration of HPV-16/18 AS04-adjuvanted vaccine with Tdap and/or MCV4 in different regimens did not interfere with the immune response to any of the vaccines and had an acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Alternatively, co-administration of current HPV vaccines with other childhood combination vaccines against multiple infectious agents should also be considered since this potentially reduces the costs of vaccine administration. Indeed, some HPV co-immunization studies thus far have shown that antibody responses from either vaccine to be non-inferior to when administered alone (30-33). …”
Section: Improving Access To Current Vaccinesmentioning
confidence: 99%
“…Alternatively, co-administration of current HPV vaccines with other childhood combination vaccines against multiple infectious agents should also be considered since this potentially reduces the costs of vaccine administration. Indeed, some HPV co-immunization studies thus far have shown that antibody responses from either vaccine to be non-inferior to when administered alone (30-33). …”
Section: Improving Access To Current Vaccinesmentioning
confidence: 99%
“…This study builds on results from other studies in adolescent girls, which have shown that the HPV-16/18 vaccine can be coadministered with other vaccines, such as DTaP-IPV, hepatitis B, Tdap, and meningococcal conjugate vaccines, without inter- fering with the immune response to either vaccine [25,36,37]. Coadministering vaccines at the same visit, rather than delivering vaccines at separate visits, will be of benefit in vaccination programs.…”
Section: Discussionmentioning
confidence: 79%
“…Since licensure, four clinical trials have evaluated immunogenicity and safety of HPV-16/18-vaccine when co-administered with other vaccines likely to be used in adolescents and adults [26][27][28][29]. Study results indicate that HPV-16/18-vaccine can be co-administered safely with meningococcal serogroups A, C, Y and W-135 polysaccharide diphtheria toxoid conjugate vaccine (Menactra TM , Sanofi-Pasteur), combined diphtheria-tetanus-acellular pertussis vaccine (with or without inactivated poliomyelitis) (Boostrix TM , Boostrix TM Polio, GlaxoSmithKline Biologicals, Belgium), hepatitis B vaccine (HBV, Engerix TM B, GlaxoSmithKline Biologicals, Belgium) or combined hepatitis A and HBV vaccine (Twinrix TM , GlaxoSmithKline Biologicals, Belgium) [26][27][28][29].…”
Section: Co-administrationmentioning
confidence: 99%